Evaluation of breastfeeding care and education given to mothers with low-birthweight babies by healthcare workers at a hospital in urban Tanzania: a qualitative study - Kyoko Tada; Yoko Shimpuku; Bruno Sunguya; Shigeko Horiuchi (BMC, 2020)
Abstract Background The total neonatal mortality in Tanzania remains high reaching as much as 44,900 deaths per year, particularly among low birthweight (LBW) babies. This makes Tanzania the fourth African country with the highest number of annual neonatal deaths. Studies have shown the advantages of breast milk for LBW babies and the effectiveness of interventions from healthcare workers (HCWs) to encourage mothers to achieve exclusive breastfeeding (EBF). Although these interventions can substantially reduce mortality in this vulnerable group, they remain insufficient in practice particularly in resource-limited countries. Therefore, there is an urgent need to establish the most appropriate interventions for mothers with LBW babies, particularly in these countries. To help address this need, we evaluated the breastfeeding care and education given to mothers with LBW babies by HCWs during hospitalization in Tanzania. Methods A qualitative study using semi-structured interviews with mothers of LBW babies at an urban hospital in Tanzania was conducted. We assessed their understanding of breastfeeding at discharge. All the interviews were conducted in local Swahili and then translated to English. Data were analyzed using content analysis. Results Among the 19 mothers interviewed, only four breastfed their baby within an hour after birth. Nine mothers received no support from HCWs when they breastfeed their baby for the first time. Ten mothers received no education on EBF, and there were mothers who misunderstood the EBF definition. Eight answered that they had difficulty breastfeeding their baby at discharge. Four mothers were dissatisfied with the care and education given by HCWs, and six mothers provided suggestions for improvements. Although six mothers had a high reliance on HCWs, they had difficulty asking HCWs questions because of their authoritative attitude and behavior. Conclusions Mothers with LBW babies need special support to increase their ability to breastfeed and ensure EBF continuance. To address the gaps between the currently provided breastfeeding interventions and the ideal breastfeeding interventions, improvements in the quality and quantity of breastfeeding care and education are required. Training HCWs to systematize standard interventions, confirming mothers' understanding, and ensuring a comfortable environment for mothers are absolutely needed.